Delving Into Pragmatic Horizons: Critical Ethnographic Research on the Assessment Culture in School - Raudienė, Irena; Mažeikienė, Natalija (Pedagogika, 2023)
In this article, we introduce Carspecken‘s (1996) pragmatic horizon analysis and validity reconstruction (PHAVR), an approach for examining taken for granted claims articulated by research participants as part of the critical ethnographic research. Validity claims are the assumptions that express implicit intentions of participants of communicative act. The application of the approach is illustrated by two examples from our fieldwork established to explore the assessment culture in one school.